Moderate salinity improves the availability of soil P by regulating P‐cycling microbial communities in coastal wetlands - Minjie Hu; Yixun Le; Jordi Sardans; Ruibing Yan; Yi Zhong; Dongyao Sun; Chuan Tong; Josep Peñuelas (Global Change Biology, 2023)
Accelerated sea‐level rise is expected to cause the salinization of freshwater wetlands, but the responses to salinity of the availability of soil phosphorus (P) and of microbial genes involved in the cycling of P remain unexplored. We conducted a field experiment to investigate the effects of salinity on P cycling by soil microbial communities and their regulatory roles on P availability in coastal freshwater and brackish wetlands. Salinity was positively correlated with P availability, with higher concentrations of labile P but lower concentrations of moderately labile P in the brackish wetland. The diversity and richness of microbial communities involved in P cycling were higher in the brackish wetland than the freshwater wetland. Salinity substantially altered the composition of the P‐cycling microbial community, in which those of the brackish wetland were separated from those of the freshwater wetland. Metagenomic sequence analysis indicated that functional genes involved in the solubilization of inorganic P and the subsequent transport and regulation of P were more abundant in coastal soils. The relative abundances of most of the target genes differed between the wetlands, with higher abundances of P‐solubilization ( gcd and ppa ) and ‐mineralization ( phoD , phy , and ugpQ ) genes and lower abundances of P‐transport genes ( pstB , ugpA , ugpB , ugpE , and pit ) in the brackish wetland. A significant positive correlation between the concentration of labile P and the abundances of the target genes suggested that salinity may, at least in part, improve P availability by regulating the P‐cycling microbial community. Our results suggest that the P‐cycling microbial community abundance and P availability respond positively to moderate increases in salinity by promoting the microbial solubilization and mineralization of soil P. Changes in microbial communities and microbially mediated P cycling may represent microbial strategies to adapt to moderate salinity levels, which in turn control soil function and nutrient balance.